2021
DOI: 10.3390/horticulturae7050116
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea Ecophysiological Responses to Accumulated Water Deficiency during the Reproductive Phase in Northeastern Pará, Brazil

Abstract: Cowpea (Vigna unguiculata (L.) Walp.) is a leguminous species widely cultivated in northern and northeastern Brazil. In the state of Pará, this crop still has low productivity due to several factors, such as low soil fertility and climatic adversity, especially the water deficiency. Therefore, the present study aimed at evaluating the physiological parameters and the productivity of cowpea plants under different water depths. The experiment was conducted in Castanhal/Pará between 2015 and 2016. A randomized bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This response to the effect of water deficit was also observed by Costa et al (2019) and Ferreira et al (2021) in cowpea, since the low availability of water in the soil causes stomatal closure by the plant in order to reduce water losses by transpiration aiming at the maintenance of cellular turgor, which contributes to the decrease of CO 2 assimilation, as it is a common route to both (COSTA et al, 2019).…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…This response to the effect of water deficit was also observed by Costa et al (2019) and Ferreira et al (2021) in cowpea, since the low availability of water in the soil causes stomatal closure by the plant in order to reduce water losses by transpiration aiming at the maintenance of cellular turgor, which contributes to the decrease of CO 2 assimilation, as it is a common route to both (COSTA et al, 2019).…”
Section: Resultsmentioning
confidence: 55%
“…According to Ferreira et al (2021), this same cultivar when subjected only to the rainfed condition in the study region (0% irrigation) in the reproductive stage showed an increase in its leaf temperature of up to 4 °C throughout the stage, while when 100% irrigated was maintained they noticed a variation of only 2 °C in leaf temperature. According to the authors, stomatal closure to prevent water loss due to transpiration is the main responsible for the increase in leaf temperature, which also contributed to the reduction in photosynthetic capacity as the decrease in CO 2 influx suggests serious consequences due to water stress (FERREIRA et al, 2021).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations